Creative Reasoning in Mathematics Problem Solving: A Systematic Literature Review of Descriptive Content Analysis Using Bibliometrics - Buaddin Hasan; Lukman Jakfar Shodiq (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Research on creative reasoning in mathematical problem-solving continues to grow significantly, as evidenced by global trends and the large number of publications identified through bibliometric analysis and the PRISMA systematic review. This study aims to analyze the trends in further research on creative reasoning and to examine aspects of creative reasoning used in mathematical problem-solving. This study employed a library research design using both bibliometric and descriptive approaches. Scientific publications related to creative reasoning served as the data sources. Data were collected through database searches using the string "creative reasoning", resulting in 1769 documents for bibliometric analysis, and 22 articles selected using the PRISMA guidelines as a systematic review instrument. Data analysis methods included bibliometric analysis to identify global trends and descriptive analysis of selected articles through the stages of identification, screening, eligibility, and inclusion. The results indicate that creative reasoning research is a current research trend in various countries and provide information on sources and documents that need to be studied as a basis for creative reasoning in mathematical problem-solving. Furthermore, the creative reasoning aspect of problem-solving is more focused on three components: novelty, plausibility, and mathematical foundation, also known as anchoring. It is concluded that these three aspects can form a more systematic theoretical framework for creative reasoning, with implications for the development of models, operational indicators, and assessment instruments for students' creative reasoning that are more specific, valid, and contextual.